Challenges and opportunities for more efficient water use and circular wastewater management. The case of Campania Region, Italy. (1st November 2021) - Colella, M.; Ripa, M.; Cocozza, A.; Panfilo, C.; Ulgiati, S.
Abstract: By 2050, global demand for water is expected to increase by some 55% due to population growth and urbanization. The utilization of large amounts of freshwater in the world, generate huge volumes of wastewater of which, globally, more than 80% is discharged without treatment, thus causing impacts on aquatic ecosystems, human health and economic productivity. More sustainable practices of wastewater management are expected as a way towards circular bioeconomy (CBE) processes, whose goal is to implement closed systems promoting the systematic use of recycling, reuse and recovery of bioproducts and by-products and the reduction of waste generation. This approach, if adopted in the water and wastewater sector, can ensure environmental, economic and social benefits. The reuse of wastewater, on the one hand, reduces the volume of wastewater and the pressure on water bodies; on the other hand, the recovery of nutrients (P or N) and/or other high value bioproducts (biogas, cellulose, biopolymers) from wastewater offers numerous advantages in terms of supplying new raw bio-based materials that can be refed back to supply chains (thus substituting fossil resources) and, at the same time, producing cleaner water to be reused. Nevertheless, while in Europe many industries have demonstrated the ability to recycle and reuse water, in many regions of Italy the sustainable management of water and wastewater is not yet consolidated. In this study we explore the available technological, economic and environmental options concerning water use and wastewater treatment and we apply them to design appropriate scenarios for improved use efficiency and circular management. A comprehensive literature review of the most promising wastewater treatment processes for resources and energy valorization was conducted. The recovery of PHAs, struvite, nitrogen and algal biomass, as potential substitutes for conventional PET, phosphate and nitrogen chemical fertilizers and electricity, respectively, in addition to reusable treated water, were hypothesized and carefully discussed. Resulting scenarios are tested against the present situation of Campania Region (situated in Southern Italy) based on population and demand statistics, in order to develop strategies and policies potentially applicable locally and elsewhere. Graphical abstract: Image 1 Highlights: Wastewater management is still a concern in many countries. Wastewater treatment may provide key options for bioproducts recovery. A review is carried out to identify resources recovery pathways from wastewater. Potential environmental benefits are identified and discussed at local level.